1988
DOI: 10.1042/cs0740123
|View full text |Cite
|
Sign up to set email alerts
|

Protein and substrate metabolism during starvation and parenteral refeeding

Abstract: 1. Healthy male volunteers underwent 10 days of hospitalized protein-calorie starvation and a subsequent 10 day repletion phase with complete intravenous nutritional support (IVF). Non-protein calories were provided as either all D-glucose or as 50% D-glucose/50% lipid. 2. In comparison with starvation, whole-body protein breakdown, as assessed by [15N]glycine, [13C]leucine and urinary excretion of 3-methylhistidine (3-MH), was diminished during IVF. The administration of parenteral nutrition did not specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…1), but the metabolic changes we observed cannot be attributed solely to hyperinsulinemia. Insulin can stimulate intracellular amino acid transport (29), but prior studies from our laboratory, with subjects made chronically hyperinsulinemic, have shown that further increases in serum insulin levels following additional carbohydrate loads does not appear to increase extremity amino acid uptake (23,30). Moreover, insulin infusion predominantly exerts an anticatabolic effect on muscle protein turnover without significantly stimulating protein synthesis (31).…”
Section: Discussionmentioning
confidence: 85%
“…1), but the metabolic changes we observed cannot be attributed solely to hyperinsulinemia. Insulin can stimulate intracellular amino acid transport (29), but prior studies from our laboratory, with subjects made chronically hyperinsulinemic, have shown that further increases in serum insulin levels following additional carbohydrate loads does not appear to increase extremity amino acid uptake (23,30). Moreover, insulin infusion predominantly exerts an anticatabolic effect on muscle protein turnover without significantly stimulating protein synthesis (31).…”
Section: Discussionmentioning
confidence: 85%
“…Despite the different substrate composition and the higher insulin levels attained with glucose, there was no significant difference in peripheral amino acid flux (i.e., forearm balance). In a similar study protocol [301] whole-body protein breakdown was decreased following parenteral nutrition in comparison with starvation. Other studies, however, suggest that the decrease in whole-body proteolysis during the infusion of glucose is mediated by increased plasma insulin concentrations and not the ambient glucose concentration or the rate of glucose utilization [302].…”
Section: Carbohydratesmentioning
confidence: 84%
“…The effects of semistarvation on body protein and lipid content have been repeatedly described ( 12,37,38), and based on these and other studies it has been suggested that starvation-elicited responses differ from the metabolic changes of cachexia. During unstressed starvation, lipid is utilized preferentially to protein, which tends to be conserved, but in cachexia there is net catabolism of both lipid and protein.…”
Section: Resultsmentioning
confidence: 99%